Square wave anodic stripping voltammetry at mercury-plated electrode. Simulation of surface morphology effects on electrochemically reversible, irreversible, and quasi-reversible processes: Comparison of thin films and microdroplets - Powell, M; Ball, J; Tsai, Y; Suarez, M; Compton, R (2000)
Mercury electroplated onto solid electrodes is widely used for electrochemical measurements. Depending on the substrate, the coating can take the form of either a uniform thin film or an assembly of microdroplets. It is interesting to ask the extent to which the morphological state can influence the nature of voltammetric responses from such electrodes. Accordingly, a general approach is developed for the numerical simulation of square wave anodic stripping voltammetry at hemispherical and uniform planar electrodes based on the backward implicit method. This is applied to the modeling of electrochemically reversible, irreversible,.and quasi-reversible redox couples. Data from the simulations are validated by comparison of characteristic properties of the voltammograms with published work for the reversible limit of the planar electrode. The variation of these characteristic features with electrode geometry and electrode kinetics is studied, and a comparison between the planar and hemispherical geometry made. Last, experimental data is presented for the nature of mercury on the surface of both iridium and copper substrates, obtained by atomic force microscopy. © 2000 American Chemical Society.